Combating problems related to library software in higher education institutions of Pakistan: An analysis of focus groups - Siddique, Nadeem; Mahmood, Khalid; Siddique, Nadeem; Mahmood, Khalid (Malaysian Journal of Library and Information Science, 2016)
The absence of standard library software is one of the main hinderance in the effective automation of libraries of Higher Education Institutions (HEIs) of Pakistan. A review of the literature does not provide the actual requirements of the libraries in Pakistan related to library software and highlights the absence of library software selection criteria. This paper explores the opinion of the experts about the current status of library software, problems faced by the libraries and needs relevant to library software in order to suggest a sustainable solution for the automation of the libraries of HEIs of Pakistan. This study was conducted using qualitative approach and three focus groups were conducted in Lahore, Islamabad and Karachi. The participants of all three focus groups comprised librarians from HEIs, Library and Information Science (LIS) experts with experience in designing and implementing library software, LIS educators with experience of teaching library automation and computer science professionals having experience with library software. A purposive sampling was made in this regard. A discussion guide was prepared on the basis of literature review and expert opinions. Data were analyzed qualitatively. The analysis of focus groups revealed that there was a shortage of library software and the libraries of HEIs were still in the process of automation. Few libraries were using standard software but most of the libraries had implemented cataloguing module only. The non-availability of standard library software, regional languages, lack of awareness, lack of funds and lack of vision in the top management of HEIs were the common problems causing hinderance in the effective automation of the libraries. The experts suggested formulation of a consortium under the umbrella of HEC that takes the resposibility of development and distribution of the software.